Amand König, a modern bookseller and publisher in Strasbourg in the second half of the Eighteenth Century - Clemente San Román, Yolanda (Revista General de Información y Documentación, 2015)
The Catalogue d'une belle collection des libres François anciens et modernes, which appears on the market in early 1777, lists the collection which Amand König, bookseller of French-German ancestry, had on sale in his bookshop in Strasbourg in 1776. With a modern mindset, visible both in the contents and the structure, König registers approximately three thousand editions of books and periodical publications from France (Paris and provinces) and Central Europe -Germany, Switzerland and the Netherlands-, most of them contemporary, although a few are editions from earlier centuries. There are books on all subjects, with the exception of physics, natural history, medicine and Catholic theology, given that these appear in other catalogues which the publisher advertises. Classified in eighteen thematic sections, the items are described with great detail and with comments on their rarity or curiosity, on their possible utility or on the elegance of the typography. Conceived, as can be seen, with a modern mindset, this catalogue is also an exceedingly rare publication in our country, in that the only known copy is conserved in the Historical Library of the Complutense University.
Keywords: ook commerce and distribution-France-18th Century; Book catalogues-France- 18th Century